Answer:
11/6=x
Explanation:
System of Linear Equations entered :
[1] y=5x-7
[2] -3x-3y=-12
Equations Simplified or Rearranged :
[1] y - 5x = -7
[2] -3y - 3x = -12
Graphic Representation of the Equations :
-5x + y = -7 -3x - 3y = -12
Solve by Substitution :
// Solve equation [1] for the variable y
[1] y = 5x - 7
// Plug this in for variable y in equation [2]
[2] -3•(5x-7) - 3x = -12
[2] - 18x = -33
// Solve equation [2] for the variable x
[2] 18x = 33
[2] x = 11/6
// By now we know this much :
y = 5x-7
x = 11/6
// Use the x value to solve for y
y = 5(11/6)-7 = 13/6
Solution :
{y,x} = {13/6,11/6}